2020
DOI: 10.2196/20631
|View full text |Cite
|
Sign up to set email alerts
|

Digital Micro Interventions for Behavioral and Mental Health Gains: Core Components and Conceptualization of Digital Micro Intervention Care

Abstract: Although many people access publicly available digital behavioral and mental health interventions, most do not invest as much effort in these interventions as hoped or intended by intervention developers, and ongoing engagement is often low. Thus, the impact of such interventions is minimized by a misalignment between intervention design and user behavior. Digital micro interventions are highly focused interventions delivered in the context of a person’s daily life with little burden on the individual. We prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 58 publications
4
43
0
Order By: Relevance
“…Similarly, research on interventions that manipulate discounting identified learning-based interventions as the most effective [ 98 ]. Using DMT to combine both assessment and intervention within one component opens up room for digital microinterventions that focus on very small and beneficial steps that people can take in their daily life [ 99 ], which may be far more acceptable than traditional long-term interventions. We plan to introduce and study different personalized and adaptive digital interventions [ 91 , 92 , 99 , 100 ] to reduce impulsive response in future studies of the DMT app.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research on interventions that manipulate discounting identified learning-based interventions as the most effective [ 98 ]. Using DMT to combine both assessment and intervention within one component opens up room for digital microinterventions that focus on very small and beneficial steps that people can take in their daily life [ 99 ], which may be far more acceptable than traditional long-term interventions. We plan to introduce and study different personalized and adaptive digital interventions [ 91 , 92 , 99 , 100 ] to reduce impulsive response in future studies of the DMT app.…”
Section: Discussionmentioning
confidence: 99%
“…We offer the term effort-optimized intervention to describe interventions that focus on generating engagement with processes of therapeutic change in the face of competing demands. Here engagement refers to the time window of the intervention itself which may vary—mostly stretching from days to months [ 12 ]—and refers to the notion that the user has to engage with the intervention for the targeted time window for it to reach a desired impact. Understanding effort optimization starts with the question “what is the lowest burden method to trigger behavior change?” For example, if one is trying to reduce arousal before bedtime, interventions may require a range of engagement levels ( Figure 1 ).…”
Section: Effort Optimized Intervention Model: Fostering Effortful Behmentioning
confidence: 99%
“…A recent report [ 11 ] on the use of MindSpot, an Australian digital mental health service may shed light on this phenomenon—the researchers reported an increase in the proportion of users looking for confidential assessment and a substantial decrease in the proportion of users looking for a traditional course-based internet intervention [ 11 ]. This suggests that many users are expecting far shorter therapeutic encounters such as microinterventions [ 12 ] compared with what would have been traditionally expected from users engaging digital health interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The "With You" digital platform delivered real-time social or mood support, consistent with the broader goal of a digital microintervention [14]. Accordingly, our study reports on assessment parameters suggested for digital microinterventions such as user engagement, with 60% of subjects providing at least two responses to mood ratings and quantitative and qualitative data.…”
Section: Comparison With Previous Studiesmentioning
confidence: 61%